Stigma and Discrimination in People Suffering with a Mood Disorder: A Cross-Sectional Study. (9th April 2012) - Lazowski, L.; Koller, M.; Stuart, H.; Milev, R.
Abstract : Background. Much research is done on the stigma of mental illness, but little research has been done to characterize these phenomena from the perspective of people with mood disorders. Objective. To characterize the extent to which individuals with bipolar disorder and depression are stigmatized, determine factors related to higher levels of stigmatization, and assess the reliability of the Inventory of Stigmatizing Experiences in a population of people with a mood disorder. Methods. Two hundred and fourteen individuals with depression and bipolar disorder were recruited from a tertiary care psychiatric hospital and surveyed using the Inventory of Stigmatizing Experiences. Results. Participants reported high levels of stigma experiences and this did not differ by diagnosis ( P = 0.578 ) . However, people with bipolar disorder reported greater psychosocial impact of stigma on themselves and their family members compared to people with depression ( P = 0.019 ) . The two subscales produced internally consistent results with both populations. Conclusion. Stigma negatively affects those with both depression and bipolar disorder but appears to have a greater psychosocial impact on those with bipolar disorder.